Clementine and the spring trip - Pennypacker, Sara, 1951- (Disney Hyperion Books, 2013)
Third-grader Clementine's school field trip to Plimoth Plantation leads to all kind of discoveries, from fourth grade eating rules to the source of the stink on the bus.